Latest generation of halogen‐containing pesticides. Issue 6 (6th March 2017) - Jeschke, Peter
Abstract: Agriculture is confronted with enormous challenges, from production of enough high‐quality food to water use, environmental impacts and issues combined with a continually growing world population. Modern agricultural chemistry has to support farmers by providing innovative agrichemicals, used in applied agriculture. In this context, the introduction of halogen atoms into an active ingredient is still an important tool to modulate the properties of new crop protection compounds. Since 2010, around 96% of the launched products (herbicides, fungicides, insecticides/acaricides and nematicides) contain halogen atoms. The launched nematicides contain the largest number of halogen atoms, followed by insecticides/acaricides, herbicides and fungicides. In this context, fungicides and herbicides contain in most cases fluorine atoms, whereas nematicides and insecticides contain in most cases 'mixed' halogen atoms, for example chlorine and fluorine. This review gives an overview of the latest generation of halogen‐containing pesticides launched over the past 6 years and describes current halogen‐containing development candidates. © 2017 Society of Chemical Industry